Academic dishonesty among Italian nursing students: A longitudinal study. (March 2017) - Macale, Loreana; Ghezzi, Valerio; Rocco, Gennaro; Fida, Roberta; Vellone, Ercole; Alvaro, Rosaria
Abstract: Considering the ethical issues related to nursing and that Ethics is an integral part of the nursing education in the degree course, one would suppose that academic dishonesty might be less frequent in nursing students than in students of other disciplines. However, several studies show that this trend of deceitful behaviour seems to be similar among the university nursing students and those of other disciplines. The aim of this study is to investigate the phenomenon of academic dishonesty in the classroom from a longitudinal perspective within a cohort of Italian nursing students. A non-experimental longitudinal design was used. All nursing students were recruited from the Nursing Science Bachelor Degree Program of a big Italian university in the centre of Italy and participants were part of an ongoing longitudinal research project which started in 2011 on nursing students' wellbeing. The results show that students get accustomed to taking academically deceitful actions. They come to consider their behaviours acceptable and normal, thereby stabilizing them, which increases the probability of stabilizing subsequent deceitful behaviours. The stability through time of academic cheating behaviours committed during higher education, within the study's timeframe, provides important perspectives into the establishment of rigorous standards of ethical and moral behaviours by the students. Highlights: Results show that the nursing students get accustomed to taking academically deceitful actions, as has been revealed in the literature. The students come to consider their cheating behaviors acceptable and normal, thereby stabilizing them. In respect to the investigation of differences in kinds of deceits, results are somewhat in agreement and somewhat in conflict with the literature. There is a correlation between cheating behaviors in the classroom and age of nursing students.